Correlation between Focal Nodular Low Signal Changes in Hoffa’s Fat Pad Adjacent to Anterior Femoral Cartilage and Focal Cartilage Defect Underlying This Region and Its Possible Implication - Chermaine Deepa Antony; John George; Wuey Min Ng; Manimalar Selvi Naicker Subramaniam (Scientifica)
Purpose. This study investigates the association between focal nodular mass with low signal in Hoffa’s fat pad adjacent to anterior femoral cartilage of the knee (FNMHF) and focal cartilage abnormality in this region. Method. The magnetic resonance fast imaging employing steady-state acquisition sequence (MR FIESTA) sagittal and axial images of the B1 and C1 region (described later) of 148 patients were independently evaluated by two reviewers and categorized into four categories: normal, FNMHF with underlying focal cartilage abnormality, FNMHF with normal cartilage, and cartilage abnormality with no FNMHF. Results. There was a significant association (p=0.00) between FNMHF and immediate adjacent focal cartilage abnormality with high interobserver agreement. The absence of focal nodular lesions next to the anterior femoral cartilage has a very high negative predictive value for chondral injury (97.8%). Synovial biopsy of focal nodular lesion done during arthroscopy revealed some fibrocollagenous tissue and no inflammatory cells. Conclusion. We postulate that the FNMHF adjacent to the cartilage defects is a form of normal healing response to the cartilage damage. One patient with FHMHF and underlying cartilage abnormality was rescanned six months later. In this patient, the FNMHF disappeared and normal cartilage was observed in the adjacent region which may support this theory.